A three-level hybrid metal/in-plane-CFRP/crossed-lamellar microstructure concept for containment applications - Häsä,R; Pinho,ST (Composites Part A: Applied Science and Manufacturing, 2019)
This paper proposes a novel hybrid metal/Carbon Fibre Reinforced Polymer (CFRP) microstructure which includes a bio-mimetic crossed-lamellar CFRP layer (with out-of-plane fibres) as well as traditional CFRP layers (with in-plane fibres). We show that this microstructure is capable of preserving its structural integrity due to the crossed-lamellar and metal layers while the in-plane fibres provides it stiffness and strength. We studied numerically and experimentally a metal hybrid/crossed lamellar block in isolation, both with aluminium and titanium for the metal. We then proceeded to create the full microstructure, including a quasi-isotropic block. Our results show that these structures can withstand very large curvatures in a pseudo-ductile way. This makes them attractive for engineering applications where structural integrity is paramount, such as for containment structures.